Maternal Smoking Leads to Larger Cleft Palate Defects - Lacerda, Rosa Helena Wanderley; Furtado, Paulo Germano Cavalcanti; Vieira, Alexandre Rezende (Frontiers in Dental Medicine, 2021)
Background: Oral clefts are birth defects that affect 500 to 1,000 livebirths depending on the geographic area. Maternal smoking increases the risk of stillbirths, prematurity, low birth weight, and oral clefts. Methods: In this case series, we measured the cleft palate defect of 10 children born from mothers who smoked during pregnancy and compared with measurements of 36 children born from mothers who did not smoke. Results: Palate defects tended to be larger in the group that the mother smoked during pregnancy. Conclusion: Smoking during pregnancy aggravates the size of the cleft defect in the palate.